2020
DOI: 10.2147/jhc.s224471
|View full text |Cite
|
Sign up to set email alerts
|

<p>Angiogenesis in Hepatocellular Carcinoma; Pathophysiology, Targeted Therapy, and Role of Imaging</p>

Abstract: Hepatocellular carcinoma (HCC) is one of the most common tumors worldwide, usually occurring on a background of liver cirrhosis. HCC is a highly vascular tumor in which angiogenesis plays a major role in tumor growth and spread. Tumorinduced angiogenesis is usually related to a complex interplay between multiple factors and pathways, with vascular endothelial growth factor being a major player in angiogenesis. In the past decade, understanding of tumor-induced angiogenesis has led to the emergence of novel ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 95 publications
1
38
0
Order By: Relevance
“…Therefore preventing/blocking abrupt angiogenesis is an effective approach for HCC prevention. (Berretta et al, 2016; Morse et al, 2018; Moawad et al, 2020). Angiogenesis has a crucial role in promoting tumor growth (HCC) by releasing VEGF leading to the development of HCC (Pan et al., 2018).…”
Section: Molecular Mechanism Of the Anticancer Effect Of Flavonoidmentioning
confidence: 99%
“…Therefore preventing/blocking abrupt angiogenesis is an effective approach for HCC prevention. (Berretta et al, 2016; Morse et al, 2018; Moawad et al, 2020). Angiogenesis has a crucial role in promoting tumor growth (HCC) by releasing VEGF leading to the development of HCC (Pan et al., 2018).…”
Section: Molecular Mechanism Of the Anticancer Effect Of Flavonoidmentioning
confidence: 99%
“…Advanced hepatocellular carcinoma (HCC) has limited treatment options, where overall survival can be improved but no cure has been found [ 119 ]. Given the highly vascular nature of HCC, anti-angiogenic therapy is currently the recommended therapy for advanced stage disease [ 120 ].…”
Section: Anti-angiogenic Therapy In the Most Common Cancersmentioning
confidence: 99%
“…Given the highly vascular nature of HCC, anti-angiogenic therapy is currently the recommended therapy for advanced stage disease [ 120 ]. Sorafenib and lenvatinib are used as first-line treatments for advanced unresectable HCC [ 119 ]; however, both have numerous side effects [ 119 ]. Regorafenib and cabozantinib are tyrosine kinase inhibitors.…”
Section: Anti-angiogenic Therapy In the Most Common Cancersmentioning
confidence: 99%
“…However, there are significant advances being made, especially with MRI, that allow imaging of angiogenesis-correlated parameters. This is beyond the scope of the current review, but interesting applications may be found in the following reviews [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%